STUDYING THE IMPORTANCE OF RUBRICS IN IMPROVING WRITING SKILLS FOR STUDENTS AT B2 LEVEL (World Bulletin of Social Sciences, 2024)
The purpose of this article to examine the value of rubrics in improving writing abilities for learners who are at the B2 level. The purpose of this study is to investigate how rubrics affect language learning, assessment procedures, and pedagogical efficacy when teaching writing to B2 level students. I hope to clarify the role of rubrics as a useful tool in assisting B2 level learners in developing their writing skills and to give educators advice on how to successfully include rubrics into their teaching practices by reviewing pertinent literature on the topic.